Development and Optimization of a Surface Sterilization Protocol for the Tissue Culture of Pleurotus Tuber-Regium (Fr) Sing. And Auricularia Auricula-Judae (British Journal of Multidisciplinary and Advanced Studies, 2017)
This study was carried out to develop and optimize a surface sterilization protocol for the sterilization of explants in the tissue culture of the edible mushrooms Pleurotus tuber-regium (Fr) Sing. and Auricularia auricula-judae. The explants were exposed to two sterilization agents; 70% ethanol (EtOH) and JIK® a locally produced bleaching solution containing 3.5% (w/v) sodium hypochlorite at concentrations of 2.5% (v/v) and 5.0% (v/v) with varying time intervals of one, two, five, ten and fifteen minutes. The results showed that treatment of explants with 5.0% (v/v) sodium hypochlorite solution for ten minutes preceded by 70% ethanol pre-treatment for two minutes gave the least explants contamination (0%) and highest explants survival (100%) for Pleurotus tuber-regium, while treatment of explants with 70% ethanol for one minute followed by 5.0% (v/v) sodium hypochlorite solution for five minutes, gave the highest survival rate (100%) and least explants contamination (0%) for Auricularia auricula-judae.